The Intercropping Using NRC Algorithm (International Journal of Engineering and Computer Science, 2020)
To predict the crop rotation for varied sorts of soil and might be done through soil fertility, water level, chemical level, climatic condition and etc. Here, mistreatment totally different data processing techniques over agriculture land soil testing is that the methodology is mistreatment wide wherever that crop is often farmed when that crop. As an example, rice is going to be cultivated at intervals seven months to eight months. The remaining time the farm won't be left empty. Another crop could cultivate for the opposite four months.